The New Parental Rights - Dailey, Anne C. (2021)
This Article sets forth a new model of parental rights designed to free children and families from the ideals of parent–child unity and family privacy that underlie the law’s expansive protection for parental rights. The law currently presumes that parents’ interests coincide with those of their children, creating an illusion of parent–child union that suppresses the very real ways in which children’s interests and identities, even at a young age, may depart from those of their parents. Expansive protection for parental rights also confines children to the private family, ignoring children’s broad range of interests beyond the family and thwarting calls for more robust state support of children subordinated by race and class. The new model of parental rights presented here brings children out from under parental control and into public view. The model conceives of parental rights in relational terms, offering greater state support for the parent–child relationship, addressing the race and class biases underlying expansive parental rights, and highlighting children’s independent interests and agency. This new approach calls for the highest scrutiny of governmental action that threatens to separate parents and children, but a less strict level of scrutiny for governmental action that intrudes upon parental authority in ways that support children’s independent interests and agency. The model also strengthens the parent–child relationship by urging a radical increase in affirmative support for all children, but especially for low-income children and children of color who suffer the most under a legal regime that privatizes the costs of children’s upbringing. This reenvisioning of parental rights has the potential to transform a broad range of laws affecting the lives of children and parents. The Article analyzes several issues of critical importance to children’s welfare: homeschooling; transgender youth medical decisionmaking; foster care; children’s peer relationships; and the forced separation of parents and children through immigration detention, child welfare removal, and parental incarceration. By calling for greater state support of both children and families, the “new parental rights” challenges the privatization of dependency; fosters diversity of family life; and respects the independent capacities, values, beliefs, and identities of all children